2020
DOI: 10.1038/s41388-020-01532-4
|View full text |Cite
|
Sign up to set email alerts
|

Fbxl8 suppresses lymphoma growth and hematopoietic transformation through degradation of cyclin D3

Abstract: Overexpression of D-type cyclins in human cancer frequently occurs as a result of protein stabilization, emphasizing the importance of identification of the machinery that regulates their ubiqutin-dependent degradation. Cyclin D3 is overexpressed in ~50% of Burkitt’s lymphoma correlating with a mutation of Thr-283. However, the E3 ligase that regulates phosphorylated cyclin D3 and whether a stabilized, phosphorylation deficient mutant of cyclin D3, has oncogenic activity are undefined. We describe the identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…CCND3 amplification was previously shown to be a marker of aggressive bladder cancer (Beltran et al, 2013), and CCND3 was also supported as urine biomarker of bladder cancer recurrence (Blanca et al, 2016). Besides, CCND3 promoted tumorigenesis and development of numerous other types of cancers (Yoshida et al, 2021;Yu et al, 2018), suggesting that CCDN3 was a wide oncogene in various cancers. Importantly, we found that cir-cMYLK could decoy miR-34a and thus increasing the expression level of CCND3.…”
Section: Discussionmentioning
confidence: 92%
“…CCND3 amplification was previously shown to be a marker of aggressive bladder cancer (Beltran et al, 2013), and CCND3 was also supported as urine biomarker of bladder cancer recurrence (Blanca et al, 2016). Besides, CCND3 promoted tumorigenesis and development of numerous other types of cancers (Yoshida et al, 2021;Yu et al, 2018), suggesting that CCDN3 was a wide oncogene in various cancers. Importantly, we found that cir-cMYLK could decoy miR-34a and thus increasing the expression level of CCND3.…”
Section: Discussionmentioning
confidence: 92%
“…As a positive control, we assessed coprecipitation of cyclin D3 since we have already established cyclin D3 as a direct Fbxl8 substrate. 10 Both c-myc and cyclin D3 were detected in Fbxl8 precipitates ( Figure 1(b )). To address binding specificity, we assessed the ability of c-myc to bind to a panel of Fbxl8 deletion mutants.…”
Section: Resultsmentioning
confidence: 98%
“… 14 Fbxl8 knockdown also accelerates G1 to S-phase entry in mammalian cells. 10 Therefore, it was critical to investigate the status of c-myc protein levels in this cell cycle-specific context. We obtained conditional knockout mice generated by Cyagen, wherein exon 3 (which encodes the F-box domain) of the Fbxl8 gene is flanked by LoxP sequences ( Figure 5(a )).…”
Section: Resultsmentioning
confidence: 99%
“…A family of F-box proteins (69 in human) serves as the substrate receptors of SCFs. Multiple F-box proteins have been reported to target cyclin D1 (reviewed by Qie and Diehl, 2020), and distinct F-box proteins have been linked to cyclin D2 and cyclin D3 (Chen et al, 2012a , 2012b; Yoshida et al , 2021 ). Still other studies have implicated the anaphase promoting complex/cyclosome (APC/C) in cyclin D1 ubiquitylation (Agami and Bernards, 2000 ; Pawar et al , 2010 ).…”
Section: Degradation Of Cyclin D By the Ubiquitin-proteasome Systemmentioning
confidence: 99%